Mediating effects of work-family psychological contract fulfillment on relationships between organizational and non-organizational factors, and organizational commitment - Mohamed Azim, Abdul Mutalib (2012)
With the increase in dual-career couples in the workforce and the lack of adequate legal contracts in the form of work-family policies, employees may hold expectations regarding employer’s obligations based on what has been promised by the organization regarding work-family benefits. Employees’ expectations of obligations from an employer may depend on psychological contracts rather than formalisms arising from laws. Despite the existence of earlier studies on psychological contract, there is still lack of studies on psychological contract that specifically addresses work-family issues. The violation of the psychological contract has received much attention while research into the fulfillment of the contract has been neglected. There is also a critical gap in the research on organizational commitment models that had examined work-family psychological contract as a mediator. This study examined the mediating effects of work-family psychological contract fulfillment on the relationships between organizational and non-organizational work-family related factors, and organizational commitment. Organizational workfamily related factors include four variables, namely family supportive organizational perceptions, family supportive supervisor, job autonomy and flexible work schedule. Non-organizational work-family related factors consist of two variables, namely work interference with family and work-family facilitation. A total of 307 executives and professionals from 15 media organizations in Klang Valley, Malaysia participated in this study. Data were analyzed using the Structural Equation Modeling procedure to assess direct and indirect relationships among variables. AMOS version 16.0 was used to perform these analyses. Four mediation models were tested to determine if the hypothesized model fit the data. Results show that work-family psychological contract fulfillment fully mediates the relationships between flexible work schedules and organizational commitment. Further, the results reveal that work-family psychological contract fulfillment partially mediates the relationships between family supportive organizational perceptions and organizational commitment, family supportive supervisor and organizational commitment, job autonomy and organizational commitment, work interference with family and organizational commitment, and work-family facilitation and organizational commitment. To conclude, the results of this study suggest that work-family psychological contract fulfillment plays a critical role in increasing employees’ organizational commitment. Overall, this study contributes to the psychological contract and workfamily literature by introducing work-family psychological contract fulfillment as an important mechanism through which work- family related factors affect employees’ organizational commitment.